KAJIAN AGRIBISNIS PENDAPATAN USAHA MADU LEBAH KELULUT”ZAHRA” (Trigona itama) DI DESA MANGKAUK KECAMATAN PENGARON KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Baparki, Ahmad; wasdiyanta; Mahyudi, Fitri; Umamah, Nurul (Chlorophyl, 2023)
This research is entitled agribusiness study of honey bee business income "zahra" (trigona itama) in mangkauk village, pengaron district, banjar district, south kalimantan province was carried out in mangkauk village, pengaron district in november 2022, using the case study method. The results obtained were costs variable (total variable cost) of rp. 66,127,666.66.- the amount of revenue (total revenue) obtained from the sale of all kelulut honey products is rp. 100,850,000.- and the amount of income (income) produced by the kelulut honey bee business for four months rp. 34,722,333.34